2018
DOI: 10.1177/0333102418776016
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind placebo-controlled randomized clinical trial of ginger (Zingiber officinale Rosc.) addition in migraine acute treatment

Abstract: Background Previous studies have demonstrated the analgesic effects of ginger in different conditions, but evidence about its efficacy in migraine treatment is scarce. Objective This study aimed to evaluate the potential of ginger to improve acute migraine as an add-on strategy to standard treatment. Methods A double-blind placebo-controlled randomized clinical trial in the emergency room of a general hospital was conducted. Patients who sought medical care at the time of migraine attack were enrolled in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 33 publications
(49 reference statements)
0
30
0
2
Order By: Relevance
“…Migraines and headaches were examined to assess the pain-relieving attributes of ginger in three RCTs. Maghbooli et al and Martins et al compared the effects of sumatriptan and placebo, respectively, both showing there was a significant difference in symptom attenuation (p < 0.05) [23,66]. Patients with low back pain and chest pain caused by percutaneous transluminal coronary angioplasty were also selected to assess the analgesic effects of ginger, and both studies concluded that ginger was a useful option for pain relief.…”
Section: Analgesic Functionmentioning
confidence: 99%
“…Migraines and headaches were examined to assess the pain-relieving attributes of ginger in three RCTs. Maghbooli et al and Martins et al compared the effects of sumatriptan and placebo, respectively, both showing there was a significant difference in symptom attenuation (p < 0.05) [23,66]. Patients with low back pain and chest pain caused by percutaneous transluminal coronary angioplasty were also selected to assess the analgesic effects of ginger, and both studies concluded that ginger was a useful option for pain relief.…”
Section: Analgesic Functionmentioning
confidence: 99%
“…Previous studies have shown the efficacy of ginger, in extract or powder, in reducing and preventing pain associated with medical conditions (8–10,17). In this study, we showed that the use of ginger extract in the prophylactic treatment of migraine was not effective in decreasing the frequency of migraine attacks.…”
Section: Discussionmentioning
confidence: 99%
“…We and others showed that ginger is effective in decreasing the intensity of migraine pain when administered as an acute strategy (17,36). In a double-blind, randomized and controlled clinical trial, Maghbooli showed that the use of 250 mg of ginger powder during migraine attacks was as effective as 50 mg of sumatriptan in relieving pain intensity 2 h after ginger intake (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 In addition, ginger was shown in a randomized placebo-controlled trial to provide better acute symptom management in addition to typical nonsteroidal anti-inflammatory drug treatment in the emergency department setting. 69…”
Section: Lifestyle and Other Therapiesmentioning
confidence: 99%